All-Trans-Retinoic Acid Combined With Valproic Acid Can Promote Differentiation in Myeloid Leukemia Cells by an Autophagy Dependent Mechanism - Benjamin, Dalyia N.; O’Donovan, Tracey R.; Laursen, Kristian B.; Orfali, Nina; Cahill, Mary R.; Mongan, Nigel P.; Gudas, Lorraine J.; McKenna, Sharon L. (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is an aggressive blood cancer with an overall survival of 30%. One form of AML, acute promyelocytic leukemia (APL) has become more than 90% curable with differentiation therapy, consisting of all-trans-retinoic acid (ATRA) and arsenic trioxide (ATO). Application of differentiation therapy to other AML subtypes would be a major treatment advance. Recent studies have indicated that autophagy plays a key role in the differentiation of ATRA-responsive APL cells. In this study, we have investigated whether differentiation could be enhanced in ATRA resistant cells by promoting autophagy induction with valproic acid (VPA). ATRA sensitive (NB4) and resistant leukemia cells (NB4R and THP-1) were co-treated with ATRA and valproic acid, followed by assessment of autophagy and differentiation. The combination of VPA and ATRA induced autophagic flux and promoted differentiation in ATRA-sensitive and -resistant cell lines. shRNA knockdown of ATG7 and TFEB autophagy regulators impaired both autophagy and differentiation, demonstrating the importance of autophagy in the combination treatment. These data suggest that ATRA combined with valproic acid can promote differentiation in myeloid leukemia cells by mechanism involving autophagy.